Beyond the developmental state: Exploring the variety of development models in East Asia - Jakob Heibel; Jonas Dominy; Jakob Kapeller (University of Duisburg-Essen, Institute for Socio-Economics (ifso), 2025)
East Asia exhibits remarkable economic heterogeneity, yet debates on the region's development have centered predominantly on the most successful cases, such as Japan, South Korea, and Taiwan, all examples of the so-called "developmental state" model, or China's economic upswing. Building on the notion that economic development follows qualitatively different trajectories that give rise to structurally distinct development models across countries, this paper employs a data-driven approach based on a multidimensional cluster analysis of 15 East Asian economies across 12 macroeconomic dimensions for the period 2000-2019 to develop a concise typology of development models in East Asia. In doing so, we find evidence for the presence of four different development models in East Asia: aside from the canonical developmental states (Japan, South Korea, Taiwan), we identify emerging economies (China, Malaysia, Thailand, the Philippines), financial hubs (Hong Kong, Singapore), and peripheral countries (Indonesia, Mongolia, Vietnam, Myanmar, Laos, Cambodia). Our results indicate that findings from past studies focusing on specific cases - such as the countries associated with developmental state model or the rise of China - can be embedded in a more general account that also considers the distinct characteristics and complementary characters of alternative development models present in the same region.
Keywords: B5; C38; F63; N15; O10; 330; Development models; developmental state; cluster analysis; path dependence; East Asia